Economic globalisation and trafficking of women in the ASEAN region : a socio-legal study - Rohani Abdul Rahim,; Tan , Swee Leng; Shereen Khan, (Fakulti Undang - Undang, 2009)
In the ASEAN region, women trafficking is problematic and challenging both for the sending and the receiving countries. The feminisation of migration results in changes in women’s role in the family, society and global economies. The growing poverty due to economic crisis and the structural adjustment programs and policies affect women’s ability to feed their families, provide facilities for their children education and pay for basic services, which force them to migrate abroad, sometimes through illegal ways. In consequence, women suffer sexual exploitation, debt bondage, abuse and threat in the course of generating income for their families. The economic globalization may also account for women trafficking problems in that it leads to gender and legal issues such as discriminations, exploitation, and domination and gender inequalities. A socio- legal approach undertaken in this study draws data from the root causes, and underlines an understanding of the lack of education and poverty, the pull and push factors, the government roles, making of effective laws, and their implementation and enforcement in order to eliminate gender inequality and discrimination. These may be regarded as human rights and the core of the efforts towards addressing the problems of women migrant workers